Bringing Marketing Back to Markets - Vadim Radaev (Экономическая социология, 2015)
This book review is devoted to the interdisciplinary volume Reconnecting Marketing to Markets edited by Luis Araujo (Lancaster University Management School), John Finch (Strathclyde University), and Hans Kjellberg (Stockholm School of Economics). The volume includes texts authored by scholars representing fields of academic marketing, economic sociology, science and technology studies, and economics. These collected texts aim to re-examine the historical link between markets and marketing and develop an integrative approach to connections between academic marketing, marketing management and markets with the help of the performativity argument.In this review, Radaev discusses the relationship between the sociology of markets and academic marketing as neighbor research areas, which focus on studying markets, but he discusses how they ignore each others’ achievements. He notes that the interest in how markets really work integrates both economic sociology and academic marketing. Then, Radaev describes the general idea of the book — marketing produces markets — and points out its four conceptual premises. First, markets are practical outcomes of organizing efforts. Second, theories about markets are performative. Third, market exchanges require framing with considerable investment in material arrangements and measurement instruments. Fourth, market agents are hybrid collectives, involving material elements and non-human objects. Finally, Radaev briefly describes the content of the book, which covers various empirical research on branding, retailing, product qualifications and so forth.